Second Order Sliding Mode Controller for Longitudinal Wheel Slip Control - Aripin, Muhamad Khairi; Norhazimi , Hamzah; Yahaya, Md. Sam; Norhazlina, Selamat; Mohd Rozaimi, Ghazali (2012)
This paper investigates the longitudinal wheel slip tracking control approach for ground vehicle. A mathematical model of a quarter vehicle undergoing a straight-line braking maneuver is used as the control model. Second order sliding mode (SOSM) control approach using super-twisting technique is proposed to manipulate the braking torque to control the wheel slip. The effectiveness of the SOSM is compared to the conventional sliding mode in the simulations of emergency straight line braking in Simulink. With the SOSM, the chattering phenomenon is eliminated, giving a smooth tracking trajectory and lower slip error and control effort.